2020
DOI: 10.3390/ijerph17239035
|View full text |Cite
|
Sign up to set email alerts
|

Rotating Night Shift Work, Exposure to Light at Night, and Glomerular Filtration Rate: Baseline Results from a Chinese Occupational Cohort

Abstract: The misalignment between the circadian clock and behavioral cycles has been implicated in pathogenesis of many diseases. The main purpose of this study is to examine the association between rotating night shift work, exposure to light at night, and glomerular filtration rate among steelworkers in north China. A total of 6869 steelworkers, aged 22 to 60 years, were included in this study. Multivariable logistic regression was used to examine the association between night shift work, the brightness of bedroom am… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Only a few previous studies have demonstrated the association between CKD and work‐related factors such as working hour, shift work, and job stress. 11 , 12 , 21 A cohort study of Chinese steelworkers reported that long‐term night shift work was associated with a higher risk of early stages of renal disease mediated by BP. 12 Furthermore, shift workers who worked in irregular, split, and rotating shifts tended to work for longer duration due to less work schedule flexibility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a few previous studies have demonstrated the association between CKD and work‐related factors such as working hour, shift work, and job stress. 11 , 12 , 21 A cohort study of Chinese steelworkers reported that long‐term night shift work was associated with a higher risk of early stages of renal disease mediated by BP. 12 Furthermore, shift workers who worked in irregular, split, and rotating shifts tended to work for longer duration due to less work schedule flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…To explore whether clinical factors mediated the association between working hours and CKD, 11 , 19 , 20 Model 3 was further adjusted for BMI, systolic blood pressure, fasting blood glucose, HOMA‐IR, uric acid, and hsCRP. To clearly elucidate the effect of working hours on CKD, 12 , 21 Model 4 was further adjusted for work‐related factors, such as work shift schedule and total KOSS‐SF score. A proportional hazards assumption was tested by examining the graphs of estimated log (−log) survival and using “ estat phtest ” command based on Schoenfeld residuals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was a cross-sectional study conducted at 11 steel production departments owned by the HBIS Group’s Tangsteel Company in Tangshan City, Hebei Province in north China. The study design and population have been described in detail in our previous studies [ 18 , 19 , 20 ]. Given that a previous study has evaluated the association between night shift work and obesity among male steelworkers in this population, the present study only included female workers [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…The main work schedule of the present study population has been introduced in detail in our previous research [ 19 , 20 ]. In brief, shift work in this study refers to rotating night shifts (the mainly four-crew-three-shift system now and historical three-crew-two-shift system).…”
Section: Methodsmentioning
confidence: 99%